Prevalence and risk factors of adverse birth outcomes in Bangladesh: Insight from a nationwide survey - Ahadul Hassan Bhuiyan Konok; Md. Shahadoth Hossain; Md. Hafizul Islam (PLoS ONE, 2026)
Background Adverse birth outcomes are significant public health concern in Bangladesh and can severely affect the health and wellbeing of children in later life. This study aimed to assess the prevalence of adverse birth outcomes (i.e., stillbirth, preterm birth, low birth weight (LBW), neonatal death) and identify the associated factors among the Bangladeshi population. Methods The study utilized nationally representative data from the Bangladesh Demographic and Health Survey (BDHS) to analyze index pregnancy outcomes for 10,254 ever-married women. The prevalence and associated factors of both composite and individual adverse outcomes were determined using appropriate statistical procedures. Results The findings indicate that 14.3% of pregnancies resulted in LBW, while 8.9% resulted in preterm birth, followed by stillbirths (1.3%) and neonatal deaths (1.3%). Overall, 14.2% of births were associated with at least one adverse outcome. Household wealth index, place of delivery, twin births, maternal desire, and regional factors were found to be associated with LBW. Factors affecting preterm birth included cesarean section delivery, wealth index, twin births and maternal desire to have children. Regarding stillbirths, associations were found with the cesarean section delivery, and twin births. For neonatal death, factors associated included cesarean section delivery, twin birth, and maternal desire. Lastly, the composite score of adverse birth outcomes was associated with wealth index, history of terminated pregnancies, place of delivery, decision-making autonomy, region, twin births, and maternal desire. Conclusion One in seven births in Bangladesh involved at least one adverse outcome, with LBW being the most prevalent. Socioeconomic disadvantage and limited women’s decision-making autonomy were consistently associated with adverse outcomes. Policies should prioritize equity-oriented maternal care, strengthen women’s autonomy, and ensure appropriate use of obstetric interventions.